Nitrogen metabolism in mycobacteria: the key genes and targeted antimicrobials - Xu, Yufan; Ma, Shiwei; Huang, Zixin; Wang, Longlong; Raza, Sayed Haidar Abbas; Wang, Zhe (Frontiers in Microbiology, 2023)
Nitrogen metabolism is an important physiological process that affects the survival and virulence of Mycobacterium tuberculosis. M. tuberculosis's utilization of nitrogen in the environment and its adaptation to the harsh environment of acid and low oxygen in macrophages are closely related to nitrogen metabolism. In addition, the dormancy state and drug resistance of M. tuberculosis are closely related to nitrogen metabolism. Although nitrogen metabolism is so important, limited research was performed on nitrogen metabolism as compared with carbon metabolism. M. tuberculosis can use a variety of inorganic or organic nitrogen sources, including ammonium salts, nitrate, glutamine, asparagine, etc. In these metabolic pathways, some enzymes encoded by key genes, such as GlnA1, AnsP2, etc, play important regulatory roles in the pathogenesis of TB. Although various small molecule inhibitors and drugs have been developed for different nitrogen metabolism processes, however, long-term validation is needed before their practical application. Most importantly, with the emergence of multidrug-resistant strains, eradication, and control of M. tuberculosis will still be very challenging.